La expansión del posesivo pospuesto a la luz de documentación navarra (y aragonesa) del siglo XIII. - ROMERO CAMBRÓN, ANGELES (Scripta, 2016)
In the first Romance texts, possessives only occur in prenominal position (e.g. (el) nuestro padre). The earliest records of postposition (e.g. padre nuestro) date back to the 13th century in Aragonese and in Navarrese dialect. This paper reports largely on documentation involving Navarrese in order to determine in what way the postpositive placement of the possessive became normal. The influence of three grammar structures has been found to trigger possessive postposition. The first structure is a possessive construction consisting of the preposition de followed by a personal pronoun (e.g. campo de nos). The second structure includes a possessive in coordination either with a prepositional phrase (nin subdito vuestro nin de la eglesia) or with another possessive (l'amor nuestra e vuestra). In this case, the possessive occurs after the noun in the natural place of a prepositional phrase. Finally, possessive postposition became a norm to compensate noun phrases including more than one modifier in prenominal position.